Tumour and tumour-like conditions of peripheral nerve origin: Ten years’ experience - Ghosh, A; Talwar, OP; Pradhan, SV (Kathmandu University Medical Journal, 2010)
Background: There are four major lesions which may arise in the peripheral nerve, namely neuroma, schwannoma, neurofibroma and malignant peripheral nerve sheath tumor. Objective: In the present study we look into the spectrum of peripheral neural tumors including their age distribution site distribution and histopathology. Materials and methods: This is retrospective study conducted in the Dept of Pathology, Manipal Teaching Hospital, Pokhara. All histopathologically diagnosed cases of primary lesions of peripheral nerve during the period Jan 2000 to Nov 2009 were reviewed and the data were analysed. Result: A total of 114 cases of peripheral neural lesions were reported in the same period. Total number of nonmalignant cases was 106 (93%) while malignant cases were 8 (7%). Among the nonmalignant cases neurofiboma was the commonest (51 cases, 45% of all) closely followed by schwannoma (39 cases, 34% of all). Among the neurofibroma cases only 2 cases had multiple neurofibromatosis while others were solitary. Among the schwannoma cases 4 were diagnosed as ancient schwannoma with presence of bizarre cells with hyperchromatic nuclei. The commonest site involved for both schwannoma and neurofibroma was scalp-face-neck followed by back. The age range for schwannoma was 16 to 75 years whereas the same for the neurofibroma cases was 2 to 82 years. MPNST cases were seen in the age range of 40 to 72 with 3 cases in upper extremity, 3 in lower extremity and 1 each in lip and cheek. 1 case was diagnosed as cellular neurofibroma with atypia in tongue and was confirmed by S100. Conclusion The majority of the tumor are benign and the commonest benign tumor was neurofibroma of sporadic type, closely followed by schwannoma. In our study the commonest site was scalp-face-neck unlike other studies. This may be due to more compliance of the patients due to cosmetic reason. ey words : Malignant peripheral nerve sheath tumor; Neurofibroma; Peripheral nerve; Schwannoma DOI: 10.3126/kumj.v8i1.3231 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 97-101